Nivolumab plus ipilimumab versus chemotherapy as first-line treatment in advanced non–small-cell lung cancer with high tumour mutational burden: patient-reported outcomes results from the randomised, open-label, phase III CheckMate 227 trial. (July 2019) - Reck, Martin; Schenker, Michael; Lee, Ki Hyeong; Provencio, Mariano; Nishio, Makoto; Lesniewski-Kmak, Krzysztof; Sangha, Randeep; Ahmed, Samreen; Raimbourg, Judith; Feeney, Kynan; Corre, Romain; Franke, Fabio Andre; et al.
Abstract: Background: In the phase III CheckMate 227 study, first-line nivolumab + ipilimumab significantly prolonged progression-free survival (co-primary end-point) versus chemotherapy in patients with advanced non–small-cell lung cancer (NSCLC) and high tumour mutational burden (TMB; ≥10 mutations/megabase). Aim: To evaluate patient-reported outcomes (PROs) in this population. Methods: Disease-related symptoms and general health status were assessed using the validated PRO questionnaires Lung Cancer Symptom Scale (LCSS) and EQ-5D, respectively. LCSS average symptom burden index (ASBI) and three-item global index (3-IGI) and EQ-5D visual analogue scale (VAS) and utility index (UI) scores and changes from baseline were analysed descriptively. Longitudinal changes were assessed by mixed-effect model repeated measures (MMRMs) and time to first deterioration/improvement analyses. Results: In the high TMB population, PRO questionnaire completion rates were ∼90% at baseline and >80% for most on-treatment assessments. During treatment, mean changes from baseline with nivolumab + ipilimumab showed early, clinically meaningful improvements in LCSS ASBI/3-IGI and EQ-5D VAS/UI; with chemotherapy, symptoms and health-related quality of life remained stable (LCSS ASBI/3-IGI, EQ-5D UI) or improved following induction (EQ-5D VAS). MMRM-assessed changes in symptom burden were improved with nivolumab + ipilimumab versus chemotherapy. Symptom deterioration by week 12 was lower with nivolumab + ipilimumab versus chemotherapy (22.3% versus 35.0%; absolute risk reduction: 12.7% [95% confidence interval 2.4–22.5]), irrespective of discontinuation. Time to first deterioration was delayed with nivolumab + ipilimumab versus chemotherapy across LCSS and EQ-5D summary measures. Conclusion: First-line nivolumab + ipilimumab demonstrated early, sustained improvements in PROs versus chemotherapy in patients with advanced NSCLC and high TMB. Clinical trial registration:NCT02477826 . Highlights: Nivolumab + ipilimumab improved patient-reported outcomes versus chemotherapy in non–small-cell lung cancer. Improvements were seen in lung cancer symptoms and in general health status. Improvements with nivolumab + ipilimumab were rapid and durable. Disease-related symptom deterioration was delayed with nivolumab + ipilimumab.